2004
DOI: 10.1200/jco.2004.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Tumor Response and Survival With Erlotinib in Patients With Non—Small-Cell Lung Cancer

Abstract: Erlotinib was active and well tolerated in this patient population, and further clinical development is clearly warranted. Cutaneous rash seems to be a surrogate marker of clinical benefit, but this finding should be confirmed in ongoing and future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
540
7
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,000 publications
(590 citation statements)
references
References 30 publications
26
540
7
17
Order By: Relevance
“…Indeed, although some authors reported a relationship between EGFR protein expression assessed by IHC and clinical benefit from EGFR tyrosine kinase inhibitors in NSCLC, 13,14 such a correlation was not confirmed by others. 11,36,37 Therefore, the predictive value of EGFR IHC in NSCLC care remains to be validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, although some authors reported a relationship between EGFR protein expression assessed by IHC and clinical benefit from EGFR tyrosine kinase inhibitors in NSCLC, 13,14 such a correlation was not confirmed by others. 11,36,37 Therefore, the predictive value of EGFR IHC in NSCLC care remains to be validated.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors produce objective response in about 12-27% of unselected patients with NSCLC. [9][10][11][12] Erlotinib has also been shown to improve the survival of patients with advanced NSCLC after a first-or secondline chemotherapy in a multicenter randomized placebo-controlled trial conducted by the National Cancer Institute of Canada. 12 Therefore, this drug has been approved by both the Food and Drug Administration and the European Medicines Agency as monotherapy for the treatment of patients with locally advanced or metastatic non-NSCLC after failure of at least 1 prior chemotherapy regimen.…”
mentioning
confidence: 99%
“…Although the reason for this discrepancy is unknown, the occurrence of skin rash has been of particular clinical relevance since several studies have correlated it with antitumour activity (Cohen et al, 2003;Saltz et al, 2003;Perez-Soler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, although the presence of an EGFR mutation may increase responsiveness to erlotinib, it is not indicative of survival benefit. Phase II trials for erlotinib and gefitinib have reported correlations between responsiveness to EGFR inhibition and patient characteristics such as gender, histologic type, race or ethnic origin, and smoking status (109,(116)(117)(118)(119).…”
Section: Egfr Inhibitionmentioning
confidence: 99%